Incidence, causes, and maternofetal outcomes of obstructed labor in Ethiopia: systematic review and meta-analysis - Asteray Assmie Ayenew (BMC, 2021)
Abstract Background Obstructed labor is a preventable obstetric complication. However, it is an important cause of maternal mortality and morbidity and of adverse outcomes for newborns in resource-limited countries in which undernutrition is common resulting in a small pelvis in which there is no easy access to functioning health facilities with a capacity to carry out operative deliveries. Therefore, this systematic review and meta-analysis aimed to estimate the incidence, causes, and maternofetal outcomes of obstructed labor among mothers who gave birth in Ethiopia. Method for this review, we used the standard PRISMA checklist guideline. Different online databases were used for the review: PubMed, Google Scholar, EMBASE, Cochrane Library, HINARI, AFRO Library Databases, and African Online Journals. Based on the adapted PICO principles, different search terms were applied to achieve and access the essential articles. The search included all published and unpublished observational studies written only in the English language and conducted in Ethiopia. Microsoft Excel 16 was used for data entrance, and Stata version 11.0 (Stata Corporation, College Station, Texas, USA) was used for data analysis. Results I included sixteen (16) primary studies with twenty-eight thousand five hundred ninety-one (28,591) mothers who gave birth in Ethiopia. The pooled incidence of obstructed labor in Ethiopia was 12.93% (95% CI: 10.44-15.42, I2 = 98.0%, p < 0.001). Out of these, 67.3% (95% CI: 33.32-101.28) did not have antenatal care follow-up, 77.86% (95% CI: 63.07-92.66) were from the rural area, and 58.52% (95% CI: 35.73- 82.31) were referred from health centers and visited hospitals after 12 h of labor. The major causes of obstructed labor were cephalo-pelvic disproportion 64.65% (95% CI: 57.15- 72.14), and malpresentation and malposition in 27.24% (95% CI: 22.05-32.42) of the cases. The commonest complications were sepsis in 38.59% (95% CI: 25.49-51.68), stillbirth in 38.08% (95% CI: 29.55-46.61), postpartum hemorrhage in 33.54% (95% CI:12.06- 55.02), uterine rupture in 29.84% (95% CI: 21.09-38.58), and maternal death in 17.27% (95% CI: 13.47-48.02) of mothers who gave birth in Ethiopia. Conclusion This systematic review and meta-analysis showed that the incidence of obstructed labor was high in Ethiopia. Not having antenatal care follow-up, rural residency, and visiting hospitals after 12 h of labor increased the incidence of obstructed labor. The major causes of obstructed labor were cephalo-pelvic disproportion, and malpresentation and malpresentation. Additionally, the commonest complications were sepsis, stillbirth, postpartum hemorrhage, uterine rupture, and maternal death. Thus, promoting antenatal care service utilization, a good referral system, and availing comprehensive obstetric care in nearby health institutions are recommended to prevent the incidence of obstructed labor and its complications.